(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
DIRETOR DA REVISTA Desembargador Federal Antonio Cedenho ASSESSOR Wladimir Rodrigues EQUIPE Francisco Oliveira da Silva Lucia Massako Y. C. Rosa Maria José F. da Rocha Mônica Maria Meloni Sícoli Renata Bataglia Garcia Simone de Alcântara Savazzoni